LC Assay for Ciprofloxacin Hydrochloride Ophthalmic Solution - Laignier Cazedey, Edith Cristina [UNESP]; Perez, Debora Pessoa [UNESP]; Perez, Jaqueline Pessoa [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Vieweg, 2009)
The objective of the current study was to develop and subsequently validate a simple, sensitive and precise reversed-phase LC method for the determination of ciprofloxacin hydrochloride in ophthalmic solution form. The chromatographic separation of ciprofloxacin hydrochloride was achieved on a Symmetry Waters C(18) column using UV detection at 275 nm. The optimized mobile phase consisted of 2.5% acetic acid solution: methanol:acetonitrile (70:15:15, v/v/v). The proposed method provided linear responses within the concentration range 1.0-6.0 mu g mL(-1) for ciprofloxacin hydrochloride. Correlation coefficient (r) for the ciprofloxacin hydrochloride was 0.9994. The precision of the method was demonstrated using intra- and inter-day assay RSD% values which were less than 5% in all instances. No interference from any components of pharmaceutical dosage forms was observed.
Keywords: Column liquid chromatography; Ophthalmic solution; Fluoroquinolone; Ciprofloxacin